Pengaruh Lingkungan Kerja dan Kompensasi Terhadap Motivasi Kerja Pegawai Badan Penelitian dan Pengembangan Daerah Provinsi Kalimantan Timur - Arni Tami; Yulia Tri kusumawati; Praja Hadi Saputra (Cattleya Darmaya Fortuna, 2025)
This study aims to analyze the influence of work environment and compensation on employee work motivation at the Regional Research and Development Agency of East Kalimantan Province. The background of the research is based on the conditions of the work environment that are not yet conducive and compensation that is considered uneven, which has the potential to reduce employee work motivation. The research method used was quantitative with an associative descriptive approach, involving the entire employee population as a sample of 67 people through saturated sampling techniques. Data were collected using questionnaires and analyzed by multiple linear regression. The results of the study show that both the work environment and compensation have a positive and significant effect partially or simultaneously on employee work motivation. The value of the determination coefficient showed that 49.4% of the variation in work motivation could be explained by the variables of work environment and compensation. The conclusion of this study is that improving the quality of the work environment and providing fair and transparent compensation play a role in shaping employee work motivation. Therefore, it is recommended that agencies strengthen internal policies that are oriented towards improving work comfort and an objective reward system to support optimal employee performance.